2005
DOI: 10.2223/jped.1341
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to identify dengue in children on the basis of Ministry of Health criteria for suspected dengue cases?

Abstract: Dengue is common among febrile diseases of childhood, with prevalence that varies according to the epidemiological situation. The clinical status of children with dengue was very similar to that of children with other nonspecific diseases. The Health Ministry criteria for suspected cases was shown to be of little use, particularly with smaller children and during periods of reduced incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…It was also found that almost half of patients studied had different causes of febrile illness with clinical manifestations similar to those of dengue, without significant differences. [17,21,22] As in our study, these studies found that acute respiratory infections to be the most frequent cause of UFS in several regions of the world. [23][24][25] In Cuba, acute respiratory infections are also important contributors to morbidity and hospitalizations, and are the primary reason for outpatient visits.…”
Section: Reprintsupporting
confidence: 71%
“…It was also found that almost half of patients studied had different causes of febrile illness with clinical manifestations similar to those of dengue, without significant differences. [17,21,22] As in our study, these studies found that acute respiratory infections to be the most frequent cause of UFS in several regions of the world. [23][24][25] In Cuba, acute respiratory infections are also important contributors to morbidity and hospitalizations, and are the primary reason for outpatient visits.…”
Section: Reprintsupporting
confidence: 71%
“…Although standardized diagnostic criteria 39 are widely used, the clinical diagnosis of DENV infection in Brazil remains notoriously inaccurate, [40][41][42] because several locally prevalent febrile illnesses may be misdiagnosed as dengue fever. Here we show that 1) dengue accounted for only 11 of 102 (10.8%) febrile episodes of non-malarial origin occurring in patients from rural and urban areas of eastern Acre, 2) even though a self-reported history of dengue diagnosis was a strong predictor of seroconversion during the follow-up (Table 4), only 4 of 24 subjects self-reporting a dengue fever episode during the follow-up actually seroconverted, and 3) most (6 of 10) of those with PRNT-confirmed DENV seroconversion reported no clinically diagnosed dengue fever episode during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In children, dengue can be asymptomatic or polysymptomatic, which may hinder the differential diagnosis. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“… 4 Thus, laboratory tests combined with a guided clinical examination, especially in endemic areas, are crucial to confirm a diagnosis, identify, and prevent outbreaks and provide early treatment for the severe forms of the disease and complications. 9 …”
Section: Introductionmentioning
confidence: 99%